The constitution of mother-daughter relationship and the development of eating disorders - MOURA, Fabiana Elias Goulart de Andrade (2023)
Based on a qualitative approach, the present study aimed to understand how mothers of adolescents eating disorders Mwith experienced the process of raising their daughters from pregnancy to their second year of age, trying to investigate the influence of those maternity experiences on the development of disorder. We interviewed mothers of six patients with anorexia nervosa who were followed up at a specialized outpatient. Maternal reports were examined by contente analysis. Results showed difficulties in holding by mothers, which led to intense suffering and feeling of powerlessness in the face of the basic needs of their daughters. Children were described as voracious and unsatisfied, what suggests that they might have experienced difficulties in coping with the care offered by their mothers in their early development experiences. Thus, results corroborate the importance of investigating early childhood experiences to understand eating disorders etiology.